Use of clofarabine for acute childhood leukemia - A Pession (Dove Medical Press, 2010)
A Pession, R Masetti, K Kleinschmidt, A MartoniPediatric Oncology and Hematology “Lalla Seràgnoli”, University of Bologna, ItalyAbstract: A second-generation of purine nucleoside analogs, starting with clofarabine, has been developed in the course of the search for new therapeutic agents for acute childhood leukemia, especially for refractory or relapsed disease. Clofarabine is a hybrid of fludarabine and cladribine, and has shown to have antileukemic activity in acute lymphoblastic leukemia as well as in myeloid disorders. As the only new antileukemic chemotherapeutic agent to enter clinical use in the last 10 years, clofarabine was approved as an orphan drug with the primary indication of use in pediatric patients. Toxicity has been tolerable in a heavily pretreated patient population, and clofarabine has been demonstrated to be safe, both as a single agent and in combination therapies. Liver dysfunction has been the most frequently observed adverse event, but this is generally reversible. Numerous Phase I and II trials have recently been conducted, and are still ongoing in an effort to find the optimal role for clofarabine in various treatment strategies. Concomitant use of clofarabine, cytarabine, and etoposide was confirmed to be safe and effective in two independent trials. Based on the promising results when used as a salvage regimen, clofarabine is now being investigated for its potential to become part of frontline protocols.Keywords: clofarabine, pediatric acute lymphoblastic leukemia, pediatric acute myeloid leukemia